Effect of social support on the association between driving status and depression differs by gender: Findings from the CLSA. (March 2021) - Stinchcombe, A.; Marchese, C.; Fossum, S.; Gagnon, S.; Naglie, G.; Rapoport, M.J.; Weaver, B.; Bédard, M.
Abstract: Introduction: Driving is a primary means of mobility. Driving cessation is associated with poor mental health outcomes, including increased risk of depression. We investigated the relationship between driving status and depression symptoms in a large Canadian sample of mid-aged and older adults. We examined whether social support buffers the relationship between driving status and depression symptoms as well as whether the effects depend on gender. Methods: Data were drawn from baseline data from the Canadian Longitudinal Study on Aging (CLSA), a large prospective study of health and aging. At baseline, 1165 participants were classified as former drivers; 40, 840 participants were classified as current drivers. Through hierarchical linear regression models, we examined whether the effect of driving status on depression symptoms (CESD-10) was moderated by social support indices (MOS-SSS). Results: Driving cessation was associated with higher symptoms of depression (B = 0.539, 95% CI, 0.237 to 0.842, p < .001). The relationship between driving status and depression symptoms was moderated by social support indices. Former driving men who reported low social support had the greatest number of depression symptoms; the effect of driving status on depression symptoms became attenuated at higher levels of social support. Conclusion: Findings highlight the importance of social support in offsetting poor mental health outcomes associated with driving cessation.